(untitled) (Yesterday & Today Journal for History Education in South Africa and abroad, 2021)
This study investigates the responses of undergraduate history students, who are also student teachers, to the use of the autobiography or biography of an apartheid resister in their third year academic history course. The motivation for using auto/ biography in the history course has been to get away from a lifeless narrative of apartheid legislation and, for students, somewhat anonymous political movements. It has also become apparent that for some students, their school exposure to apartheid history was dulled by narrow focus and repetition. The study examines the reasons for student choices of their human subject, and how their understanding of apartheid resistance and their feelings about it are affected by engaging with life stories. It also investigates the extent to which the historical thinking and historical sense of these students both shapes and is influenced by their engagement with auto/ biography as a form of history. It notes significant levels of interest and empathy generated by the study of apartheid resistance through the life stories, as well as notable levels of commitment and enthusiasm in doing the related tasks. There is some evidence of an ability to critique auto/biography as history - as representation; but largely there is an acceptance of the life story of the ‘hero of the struggle’ they studied as truthful.